The Influence of Self-Control, Income, and Financial Management Behavior on the Financial Well-Being of Scholarship Recipients at UINSU - Wulandari, Wulandari; Rahma, Tri Inda Fadhila; Hasibuan, Faisal Umardani (Universitas Muhammadiyah Sorong, 2026)
This study aims to assess how self-discipline, earnings, and financial management strategies affect the financial wellness of scholarship recipients at UIN Sumatera Utara. A quantitative approach is utilized, applying multiple linear regression for data evaluation with the help of SPSS 27. Information is collected using an online survey administered via Google Forms, focusing on a group of 86 scholarship recipients at UIN North Sumatera. The results indicate that self-discipline positively influences financial wellness, earnings also positively contribute to financial wellness, and financial management behavior positively affects financial wellness as well. In combination, self-discipline, earnings, and financial management strategies have a significant impact on financial wellness. This research underscores the significance of individual discipline, financial resources, and sound management strategies as key elements for enhancing financial wellness.